2005
DOI: 10.1158/0008-5472.can-05-0912
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Receptor Regulation of Epidermal Growth Factor Signaling through Src in Breast and Prostate Cancer Cells: Steroid Antagonist Action

Abstract: Under conditions of short-term hormone deprivation, epidermal growth factor (EGF) induces DNA synthesis, cytoskeletal changes, and Src activation in MCF-7 and LNCaP cells. These effects are drastically inhibited by pure estradiol or androgen antagonists, implicating a role of the steroid receptors in these findings. Interestingly, EGF triggers rapid association of Src with androgen receptor (AR) and estradiol receptor A (ERA) in MCF-7 cells or ERB in LNCaP cells. Here, we show that, through EGF receptor (EGFR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
175
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 170 publications
(181 citation statements)
references
References 28 publications
6
175
0
Order By: Relevance
“…In addition, AR or ER inhibition by steroid antagonists or siRNA prevents EGF-triggered DNA synthesis and cytoskeletal changes (Migliaccio et al, 2005). This is confirmed by the experiments in Figure 5 showing that steroid antagonists inhibit EGF-induced DNA synthesis in LNCaP and MCF-7 cells.…”
Section: Resultssupporting
confidence: 70%
See 4 more Smart Citations
“…In addition, AR or ER inhibition by steroid antagonists or siRNA prevents EGF-triggered DNA synthesis and cytoskeletal changes (Migliaccio et al, 2005). This is confirmed by the experiments in Figure 5 showing that steroid antagonists inhibit EGF-induced DNA synthesis in LNCaP and MCF-7 cells.…”
Section: Resultssupporting
confidence: 70%
“…It has been recently reported that, in LNCaP and MCF-7 cells, EGF-induced signaling requires the association of AR and ER with Src (Migliaccio et al, 2005). In addition, AR or ER inhibition by steroid antagonists or siRNA prevents EGF-triggered DNA synthesis and cytoskeletal changes (Migliaccio et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations